The Effect of Thespesia populnea Against Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase Receptor by Study In Silico - I Made Prasetya Kurniawan; Prawesty Diah Utami; Risma Risma (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Indonesia is a country that has abundant natural resources; one of them is the Baru laut plant which is the latest breakthrough because it has an active substance that can be used as an anti-malaria medicine. It is very beneficial because there has been a case of resistance of artemisinin derivatives in Indonesia. The purpose of this study was to determine the potential of active compounds in Baru laut plants (Thespesia populnea (L.) Soland ex. Correa) against the Plasmodium falciparum enoyl acyl carrier protein reductase receptor in P. falciparum through in silico studies. This research is purely experimental using the One-Shot Experimental Study research design method. Observations were only made once between the variables studied through three analyzes, namely prediction analysis of active compound content, prediction analysis of the mechanism of action of active compound content, and prediction analysis of ADME active compound. The study results show that there are three active compounds in Baru laut plants that have antimalarial potential. The three compounds include gossypol, linoleic acid, and beta-sitosterol, have their respective potential in becoming a malaria drug. This study concludes that Baru laut plants have potential as anti-malaria drugs.